THE INFLUENCE OF PRODUCT QUALITY, PRICE, AND STORE ATMOSPHERE ON CONSUMER PURCHASING DECISIONS - Janah, Daimatul; Muslihudin, Muslihudin; Nurhuda, Abid; Nurdiyanto, Nurdiyanto (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2023)
Technological and industrial developments require every company to be able to compete. In improving the quality of a company, it is necessary to pay attention to product quality, price, and store atmosphere to attract consumers. This research aims to analyze the influence of product quality, price, and store atmosphere on consumer purchasing decisions at the Cik-Cik Style Store in Kartasura. This research uses quantitative research methods. Data were analyzed using multiple linear regression using IBM SPSS Version 26 software. The research results showed that product quality had a positive and significant effect on consumer purchasing decisions. This is proven by the results of the probability significance value of the product quality variable of 0.000<0.05 with a coefficient of 0.628. Furthermore, price has a positive and significant effect on consumer purchasing decisions. This is proven by the results of the significance of the influence of price on consumer purchasing decisions of 0.000 < 0.05. Store atmosphere also has a positive and significant effect on consumer purchasing decisions. This is proven by the results of the significant influence of store atmosphere on consumer purchasing decisions of 0.000 < 0.05. Lastly, product quality, price, and store atmosphere simultaneously influence consumer purchasing decisions. This is proven by the results of the F test showing the calculated F value > F table of (93.155 > 2.66).